Recent developments in the research on biomarkers of cholangiocarcinoma in primary sclerosing cholangitis - Wannhoff, Andreas; Gotthardt, Daniel (Clinics and research in hepatology and gastroenterology, 2019)
Primary sclerosing cholangitis (PSC) is characterized by a chronic inflammatory process of the bile ducts of unclear aetiology. It is often complicated by cholangiocarcinoma (CCA) with a dismal prognosis. Early detection of CCA is important because treatment options for advanced disease are limited. Besides the established markers, like CA19-9, recent developments have been made using latest technologies. This review summarizes the recent advances and remaining limitations of biomarkers of CCA in PSC.